Proceedings of SPE International Symposium on Formation Damage Control 2000
DOI: 10.2523/58750-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Induced Formation Damage in Oilfield Reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractFormation damage in terms of physio-chemical reactions such as asphaltene deposition, scale precipitation and fines migration for example, is relatively well understood. In contrast to this the effects of indigenous and introduced microbes and their role in oilfield formation damage is less well understood. Oilfield microbes, especially the S.R.B. (sulphate reducing bacteria) have been identified from many oilfields world wide (indigenous) and have been isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Chakraborty et al [36] concluded that a major explanation behind this phenomenon may be bioclogging-induced formation damage, which can occur mostly when the dominant factor-porosity-is lower than 24% [36]. Wood and Spark [37] studied bacterial induced damage-reaction mechanism in producing formations. They were utilising microbial bottle and flood analysis conducted at different temperatures up to the actual producing formation temperature modelled the microbial formation damage mechanisms.…”
Section: Biological Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chakraborty et al [36] concluded that a major explanation behind this phenomenon may be bioclogging-induced formation damage, which can occur mostly when the dominant factor-porosity-is lower than 24% [36]. Wood and Spark [37] studied bacterial induced damage-reaction mechanism in producing formations. They were utilising microbial bottle and flood analysis conducted at different temperatures up to the actual producing formation temperature modelled the microbial formation damage mechanisms.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…They were utilising microbial bottle and flood analysis conducted at different temperatures up to the actual producing formation temperature modelled the microbial formation damage mechanisms. Wood and Spark [37] observed that native microbes can interact in different ways and induce formation damage reactions based on the different temperature values in the different regions of the reservoir, whereby those regions of the reservoir with temperature values of ~120 °C are habitats for pore-lining native bacteria, capable of inducing insignificant damage reactions, but those regions of the reservoir with temperature values of ~60 °C are home to a small number of pore-blocking microbes, which can induce significant damage reactions only when the population of the microbial community becomes large enough to occlude narrow micropore networks [37].…”
Section: Biological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbes are known to survive and thrive under extreme conditions, produce hydrogen sulfide and cause souring of the wells and reduce hydrocarbon quality (1,2,3) . Microbes also have other negative effects; causing plugging or formation damage (4,5,6) and corrosion (7,8,9) . The impact of this biogenic fouling on infrastructure is expensive.…”
Section: Introductionmentioning
confidence: 99%